The Effects of Transformational Leadership, Organizational Communication and Career Development On Sustainability Employee Performance - Malau, Christiani Noni; Anik Herminingsih (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study examines the influence of transformational leadership, organizational communication, and career development on sustainability employee performance, with team collaboration as a mediating variable at the Department of Transportation of Banjarmasin City. The population of this study consisted of honorary employees, with a total sample of 157 respondents. The data were analyzed using the Structural Equation Model-Partial Least Square (SEM-PLS) method. The results show that transformational leadership, organizational communication, and team collaboration have a positive and significant effect on sustainability employee performance. However, career development does not have a significant effect on sustainability employee performance. Furthermore, team collaboration does not significantly mediate the relationship between transformational leadership, organizational communication, and career development on sustainability employee performance.